2015
DOI: 10.1002/rcs.1651
|View full text |Cite
|
Sign up to set email alerts
|

Introducing robotic surgery into an endometrial cancer service–a prospective evaluation of clinical and economic outcomes in a UK institution

Abstract: Background We have assessed how the introduction of robotics in a publicly funded endometrial cancer service affects clinical and economic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 15 publications
2
36
5
1
Order By: Relevance
“…The exact allocation of different costs into each of these categories is described previously. 4 These were allocated into one of nine categories, including costs for wards, high-dependence care, medical staffing, theaters, drugs and pharmacy, blood products, imaging, pathology, and rehabilitation therapy. Outcomes from 24 of the patients unstratified by BMI have been reported in another paper on a different subject.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact allocation of different costs into each of these categories is described previously. 4 These were allocated into one of nine categories, including costs for wards, high-dependence care, medical staffing, theaters, drugs and pharmacy, blood products, imaging, pathology, and rehabilitation therapy. Outcomes from 24 of the patients unstratified by BMI have been reported in another paper on a different subject.…”
Section: Methodsmentioning
confidence: 99%
“…Outcomes from 24 of the patients unstratified by BMI have been reported in another paper on a different subject. 4 All operations included a hysterectomy and removal of the Fallopian tubes and ovaries. It is policy to perform a limited pelvic lymphadenectomy in patients with more than grade 1 or stage 1a disease although it is often not performed on an individual basis in patients who are elderly or who have excess comorbidity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a variety of cost factors were included in the calculations. A careful analysis of endometrial cancer from Great Britain, however, has recently reported the contrary (48). There is consensus about the fact that maximum utilization of the system and a well-coordinated team with efficient processes of selection and organization can reduce the costs to the level of open surgical techniques.…”
Section: Cost Efficiency Of Robotic Surgerymentioning
confidence: 99%